(untitled) (Revista Peruana de Investigación Educativa, 2009)
this study sought to analyze the relationship between family dynamics and schooling, distinguishing between the participation of parents in activities related to school and the within household allocation of time to educational activities. the fieldwork was done with 80 families of 10 communities in Quispicanchis, Cuzco. We register within household activities – at the beginning and during the school year-, and carried out interviews and surveys. Some of the main results are that we found relatively strong linkages in the more formal aspects of the family-school relationship. Also those families who communicate only in Quechua are less involved in school activities. We also found that the allocation of time to educational activities is relatively low and that less time allocated to educational activities seems to be associated to more time dedicated to labor activities. Also, we found quite heterogeneity in after school activities, although we can distinguish some patterns such as that those kids living in upper altitude communities with more labor activities have less time dedicated to educational activities.